2014
DOI: 10.1051/ijmqe/2014013
|View full text |Cite
|
Sign up to set email alerts
|

Development of a system to increase the legal metrological control of measuring instruments in Brazil

Abstract: Abstract. This article presents the development of a system used by the Brazilian Network of Legal Metrology and Quality -INMETRO and its delegated public bodies to increase the coverage of mandatory periodic verification on measuring instruments in Brazil, especially non automatic weighing instruments. Based on a governmental database of active establishments that allowed the choice of an specific economic activity, the system provides a list of establishments where measuring instruments are used to commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…A Metrologia Aplicada às Ciências da Vida, ocupada das medições de parâmetros biológicos, é considerada um novo ramo do conhecimento (LUIZ et al, 2004). No Brasil as ciências metrológicas possuem ainda uma atuação fundamentalmente direcionada à regulamentação legal, em sua interação com o setor saúde (SORATTO et al, 2014).…”
Section: Resultsunclassified
“…A Metrologia Aplicada às Ciências da Vida, ocupada das medições de parâmetros biológicos, é considerada um novo ramo do conhecimento (LUIZ et al, 2004). No Brasil as ciências metrológicas possuem ainda uma atuação fundamentalmente direcionada à regulamentação legal, em sua interação com o setor saúde (SORATTO et al, 2014).…”
Section: Resultsunclassified
“…It is reported that the lack of metrological control or verification, as well as the inadequate frequency of verification of these instruments, are generally the cause of measurement errors, followed by an erroneous or inadequate diagnosis, which puts the well-being of the patient at risk. In another work [5], it is reported that INMETRO uses a system to perform periodic verifications of measuring instruments, pointing to a legal metrological control where the model approval processes as recommended by OIML R16-1, show the absence of the estimate. uncertainty for the case of sphygmomanometers.…”
Section: Introductionmentioning
confidence: 99%